STRATEGI GURU DALAM MENGINTERNALISASI NILAI-NILAI KEARIFAN LOKAL UNTUK PENGUATAN KARAKTER SISWA SEKOLAH DASAR - Ratri Nuryani Qudwatullathifah; Tria Aditia Nugraha; Cucuh Miftahurrohmah (Program Studi PGSD Universitas Flores, 2025)
The implementation of character education in schools often faces various obstacles, such as the lack of approaches that are aligned with the local cultural context. This study aims to explore the strategies used by teachers in developing students' character in elementary schools through character education based on local wisdom, as well as to analyze the strategies employed and the challenges faced by teachers. The research method used is a descriptive qualitative approach, with data collection techniques including in-depth interviews, observations, and document studies. The subjects of this study are elementary school teachers who have implemented character education based on local wisdom. The findings of the study indicate that teachers utilize methods such as folktales, local legends, and traditional games to integrate aspects of local wisdom, such as cooperation, honesty, responsibility, and tolerance, into the teaching and learning process. However, teachers face several challenges, including limited learning resources and the lack of training that aids in the implementation of character education based on local wisdom. The findings of this study suggest that character education grounded in local wisdom is effective in shaping students' character according to their culture and supports social learning theory as well as ecological development theory. This study recommends further support from educational stakeholders in providing facilities and training to strengthen the implementation of character education based on local wisdom in elementary schools.